A Preliminary Study Examining the Prevalence and Perceived Intensity of Morally Injurious Events in a Veterans Affairs Chaplaincy Spiritual Injury Support Group. Issue 2 (3rd April 2019) - Kopacz, Marek S.; Adams, Mary S.; Searle, Robert; Koenig, Harold G.; Bryan, Craig J.
Abstract : The aim of this descriptive study was to examine the prevalence and perceived intensity of potentially morally injurious events (PMIEs) in a group of VA chaplaincy service users. A secondary aim was to examine the relationship between PMIEs, spiritual injury, and religiosity. A convenience sample of veterans ( n = 84), participants in a spiritual injury support group, completed the Moral Injury Events Scale (MIES). Most individuals also completed the Duke University Religion Index (as a measure of religiosity) and Spiritual Injury Scale. Results suggest a high prevalence of PMIEs among participants. These PMIEs were also higher in perceived intensity compared to other military and veteran samples. No significant correlations were identified between MIES scores and either religiosity or spiritual injury. These findings draw attention to the engagement of chaplains in supporting veterans affected by PMIEs. Implications for future research are discussed.